Assessing the acceptability of a novel dry powder inhaler: A multicentre study in adult asthmatic patients using routine bronchodilator therapy - Allen, M; Anderson, P; Barnes, N; Campbell, J; Laszlo, G; Millar, A; Morice, A; Peake, M; Rogers, T; Stern, M; Stradling, J; Ward, M; et al. (2001)
Objective: To assess patient acceptability of a novel dry powder inhaler (DPI), Clickhaler® (Innovata Biomed Ltd., the Respiratory Division of ML Laboratories PLC) in routine clinical use as a first-line bronchodilator treatment. Design: In a multicentre open label study, asthma patients taking bronchodilators via a metered dose inhaler (MDI) or DPI (Turbohaler®) were given salbutamol via the Clickhaler®. Questionnaires before and after four weeks of treatment were used to assess the clinicians' and patients' opinions of the device. Subjects: 184 asthma patients aged ≥18 years, showing a good DPI technique. Results: Of the 175 patients completing the study, 121 found the Clickhaler® as easy (30%) or easier (39%) to use than their pre-study inhaler and 87 patients (50%) liked the Clickhaler® as much as (15%) or more than (35%) their pre-study inhaler. Investigators considered it more suitable (26%)/as suitable (39%) as the pre-study device for 65% of patients. Correct technique was easy to teach and was maintained by 98% of the patients after four weeks. Conclusion: The Clickhaler® is easy to operate and well accepted by adult asthma patients.